Elit Tajen Dalam Pemilihan Anggota Legislatif Kota Denpasar Tahun 2019 - Yudi Pratama, I Putu Krisna; Pramana, Gede Indra; Mahaswari Jayanthi Mertha, Anak Agung Sagung Mirah (Jurnal Nawala Politika; Vol 1 No 1 (2022): Jurnal Ilmu Politik 2022, 2022)
This research aims to determine the role of the tajen tradition in the 2019 legislative elections in Denpasar. This study is framed using the theory elites by Suzanne Keller as an analytical tool for the problems in this study. The research method used in this research is qualitative descriptive research with primary and secondary data usage, because it describes and illustrates phenomena that exist, both natural and human engineering. The results of this study are: first, there is a patron-client and modular relationship between Karisantika and tajen fans which makes him have a strategic role as an elite. Second, Karisantika's strategic role in tajen makes political mobilization smoother in winning elections. Third,. Political mobilization is getting smoother because of the legality that is played out, so that the Tajen fans feels protected and fosters a good image for Karisantika.